Automated Beer Parlour Billing System using VB.NET and MS Access Database - Walter, Ndueso (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The growing need for precision and efficiency in hospitality management has driven small and medium-sized businesses to adopt digital billing solutions. This study presents the design and implementation of an Automated Beer Parlour Billing System developed using Visual Basic .NET and Microsoft Access. The system replaces error-prone manual billing methods by integrating automated billing, inventory control, and sales tracking into a unified desktop platform. Development followed a structured methodology encompassing requirement analysis, modular programming, and systematic testing to ensure functional accuracy and security. The system architecture employs a two-tier client–server model, featuring a presentation layer for user interaction and a data access layer for database operations, enabling consistent real-time data flow. Key modules—Login, Product Management, Point of Sale (POS), Receipt Generation, Sales Reporting, and User Management—collectively enhance operational speed, billing accuracy, and accountability.Implementation results show that automation significantly improved transaction efficiency, reduced human error, and strengthened inventory management. The interface design promotes usability, requiring minimal technical expertise while supporting role-based access and encrypted authentication. Evaluation confirmed compatibility across multiple Windows environments and reliable performance even on low-specification systems. Discussion highlights that the system’s modular structure not only simplifies maintenance but also aligns with modern design principles for small-scale business software. Although limited by its desktop architecture and database scalability, the system offers a robust foundation for future web or cloud migration. Overall, the project demonstrates that cost-effective technologies like VB.NET and Microsoft Access can deliver practical, scalable automation for small businesses—enhancing accuracy, transparency, and decision-making in hospitality operations.